COMPARATIVE ANALYSIS OF ISLAMIC ETHICAL PRINCIPLES AND INTERNATIONAL HUMANITARIAN NORMS IN MODERN CONTEXTS - AYZZARO', ARRINDA LUTHFIANI (LPPM STAI Muhammadiyah Probolinggo, 2025)
Humanitarian challenges in the contemporary era increasingly demand ethical frameworks that are both universal and contextually relevant. While international humanitarian norms provide globally recognized standards, Islamic ethics offer a distinctive moral foundation grounded in divine accountability and social responsibility. This study aims to conduct a comparative analysis of Islamic ethical principles and international humanitarian norms in modern contexts. Employing a qualitative research design, the study draws upon in-depth interviews with Islamic scholars and humanitarian practitioners, complemented by document analysis of relevant texts and guidelines. The findings reveal significant areas of convergence, such as the shared emphasis on human dignity, justice, and the protection of vulnerable groups. However, divergence emerges in the epistemological grounding, where Islamic ethics prioritize transcendental values rooted in revelation, while international norms emphasize secular and legalistic frameworks. The study highlights both opportunities and tensions in integrating these perspectives, particularly in contexts where global standards must engage with religious traditions. Theoretically, the research contributes to the discourse on comparative ethics by bridging Islamic thought and global humanitarian paradigms. Practically, it offers insights for policymakers, NGOs, and educational institutions seeking to develop more inclusive and culturally sensitive humanitarian approaches. Keywords: Islamic ethics, humanitarian norms, comparative analysis, global ethics, qualitative study